Understanding Police Officers’ Usage of High-Visibility Safety Apparel: The Role of Safety Ethics and Professional Appearance - Mijin Kim; Christina Soyoung Song (Safety, 2021)
High-visibility safety apparel (HVSA) is personal protective clothing that provides visual conspicuity to reduce police officers’ risk of fatality or injury from road traffic accidents. Under the current U.S. Department of Transportation’s Federal Highway Administration regulations, police officers on or near Federal-Aid highways are mandated to wear HVSA to enhance their visibility. Although wearing HVSA can significantly prevent traffic-related fatalities among police officers, studies have shown that they do not consistently, or ever, wear it. This study identifies factors influencing HVSA noncompliance among officers by exploring their perceptions of its use and efficiency. Ninety-eight police officers completed a field survey in four cities in Yavapai County, Arizona; their responses were analyzed via predictive decision tree modeling. The results indicated that officers’ HVSA-wearing behavior can be predicted by safety ethics, professional appearance, occupation risk, functionality of HVSA, and safety education. Among these predictors, safety ethics and professional appearance were the most important factors in forecasting officers’ HVSA-wearing behavior. Our study contributes to enhancing knowledge about the psychological aspects of officers’ HVSA-wearing behavior and provides implications for improving their traffic safety policies and compliance in the law enforcement community.